Improvements Over Two Phase Shortest Path Algorithm - Qureshi, M.A.; Hassan, M.F. (2010)
Shortest path is an old classical problem in the area of theoretical computer science. This work is the continuation of the work done previously by the authors and presents two possible improvements in the existing algorithm. The introduced improvements which are simple and fit in easily into the existing algorithm prove to improve the complexity level. The need of improvement is discussed in detail and the expected improvement in overall processing time is shown with the example.